ARTIFICIAL LIGHTING COMPOSITION FOR CITY GARDEN Study Case: Taman Kota 1, BSD, Tangerang - Wicaksono, Emanuel Agung; Gunawan, Ferry (Ide dan Dialog Desain Indonesia (Idealog), 2020)
In general in Indonesia, especially in BSD, Tangerang, existing public parks are not visied during night time by the general public. One of the reasons are non-existing or inadequately lighting design at night which cause the visitors to feel unsafe and unable to do any activities well. The purpose of this research is to give guidance on lighting design according to national or international standard for public space which in this case for one park in BSD, Tangerang. The objective of this research is to create framework for optimal lighting design that creates a sense of safety and optimal lighting for night time activities. The method used in this research is to use the Relux software. Taman Kota 1 BSD has the potential to be opened at night to the surrounding community if it has adequate and safe lighting.Keywords: lighting design, park, design framework, design, composition